Governance Of The Fadllillah Islamic Boarding School: Implementation Of Quality Culture Towards Educational Excellence - Agus Salim (Institut Agama Islam An-Nawawi Purworejo, 2024)
Pesantren based education consistently emphasizes Islamic values ​​in all its aspects, according to the mandate of the constitution and the National Education Mission, as regulated in the SISDIKNAS Law No. 20 of 2003 Article 5 Paragraph 1. This research aims to comprehensively describe the planning, implementation, obstacles, and solutions to implementing a quality culture at the Fadllillah Islamic Boarding School (PP) to achieve a level of excellence. The research method used is a qualitative approach with a case study type. Respondents to this research included leaders, directors of TMI (Tarbiyyatul Mu'allimin Al-Islamiyah), student care staff, teachers, and students, with a total sample of 44 people. Data was collected through a survey that combined in-depth interviews, observation, and document analysis as the main instruments. Data analysis refers to the Miles and Huberman interactive model. The research results show that the Fadllillah Islamic Boarding School in Tambak Sumur, Sidoarjo, has high standards in quality culture planning to create a superior Islamic boarding school. Concrete steps have been taken, including arranging subject matter, learning processes, assessment, graduate competency, management, and financing with high seriousness. Apart from that, this Islamic boarding school also emphasizes Islamic boarding school values ​​such as a sincere spirit, simple living, independent spirit, and Islamic brotherhood. With this approach, Pondok Pesantren Fadllillah has maintained and improved its reputation as a trusted educational institution with a solid and integrated quality culture.